Implementasi Fungsi Manajemen dalam Penyelenggaraan Dies Natalis HMM-UNPAM Ke-20 Bertema “Bring Me Home” sebagai Upaya Memperkuat Rasa Memiliki dan Solidaritas Organisasi - Tamala Setiarini; Livia Anggun Nazilah; Nayaka Sheridan Husain; Dwi Apriyanti; Lailatul Hikma Roniawan (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study analyzes the implementation of management functions—Planning, Organizing, Actuating, and Controlling (POAC)—in organizing the 20th Dies Natalis of HMM-UNPAM themed "Bring Me Home," and its implications for organizational solidarity. Using a descriptive qualitative approach with a case study design, data was gathered through triangulation involving documentation study, participatory observation, and in-depth interviews. The results indicate that meticulous planning of micro-timing and equitable organizing through transparent division of responsibilities establish a strong foundation for teamwork. During the actuating phase, mobilizing meaningful ceremonial sessions effectively dismantles bureaucratic barriers and minimizes interpersonal rigidities among members. This success is finalized by a strict controlling function over the rundown and the collaborative cleanup agenda ("Operasi Semut"). In conclusion, structured and participatory event management significantly contributes to internalizing organizational values, expanding member engagement, and consolidating solidarity.